Seasonal atmospheric deposition and air–sea gas exchange of polycyclic aromatic hydrocarbons over the Yangtze River Estuary, East China Sea: Implications for source–sink processes. (April 2018) - Jiang, Yuqing; Lin, Tian; Wu, Zilan; Li, Yuanyuan; Li, Zhongxia; Guo, Zhigang; Yao, Xiaohong
Abstract: In this work, air samples and surface seawater samples covering four seasons from March 2014 to January 2015 were collected from a background receptor site in the YRE to explore the seasonal fluxes of air– sea gas exchange and dry and wet deposition of 15 polycyclic aromatic hydrocarbons (PAHs) and their source–sink processes at the air–sea interface. The average dry and wet deposition fluxes of 15 PAHs were estimated as 879 ± 1393 ng m −2 d −1 and 755 ± 545 ng m −2 d −1, respectively. Gaseous PAH release from seawater to the atmosphere averaged 3114 ± 1999 ng m −2 d −1 in a year round. The air– sea gas exchange of PAHs was the dominant process at the air–sea interface in the YRE as the magnitude of volatilization flux of PAHs exceeded that of total dry and wet deposition. The gas PAH exchange flux was dominated by three-ring PAHs, with the highest value in summer and lowest in winter, indicating a marked seasonal variation owing to differences in Henry's law constants associated with temperature, as well as wind speed and gaseous-dissolved gradient among seasons. Based on the simplified mass balance estimation, a net 11 tons y −1 of PAHs (mainly three-ring PAHs) were volatilized from seawater to the atmosphere in a ∼20, 000 km 2 area in the YRE. Other than the year-round Yangtze River input and ocean ship emissions, the selective release of low-molecular-weight PAHs from bottom sediments in winter due to resuspension triggered by the East Asian winter monsoon is another potential source of PAHs. This work suggests that the source–sink processes of PAHs at the air– sea interface in the YRE play a crucial role in regional cycling of PAHs. Highlights: Year-round deposition and air–sea exchange fluxes of 15 PAHs were determined. PAH air– sea gas volatilization is the dominant process at the air– sea interface. Resuspension of sediment in water column is an important source of PAHs.